Foreword - Gabrielle Appleby; Alexander Reilly; Sean Brennan (Legal Education Review)
The development by law students of an ability to engage in critical thinking is highly valued within both the legal academy and the legal profession because it enhances the ability of law students to think clearly, objectively and independently, whether they are seeking to understand legal doctrine, solve legal problems or improve access to justice. This article draws upon the authors’ experiences as law teachers and upon the critical thinking literature to present detailed criteria for the measurement of an ability to engage in critical thinking about law, and then applies those criteria in the design of a marking rubric that facilitates a whole-of-curriculum approach to the development of critical thinking skills by law students.